Photochemical Activation of Sulfur Hexafluoride: A Tool for Fluorination and Pentafluorosulfanylation Reactions - Rombach, David; Wagenknecht, Hans-Achim (Synthesis, 2022)
The photoactivation of notoriously inert sulfur hexafluoride represents a challenge for photochemistry. This short review summarizes recently published efforts and the corresponding photochemical mechanisms for switching between the fluorination and pentafluorosulfanylation reactivity of organic substrates.1 Introduction2 Sulfur Hexafluoride (SF6)3 The Pentafluorosulfanyl (SF5) Group4 Photoredox Catalytic Activation of SF65 Conclusions
Keywords: photochemistry; photocatalysis; fluorination; electron transfer; light; sulfur hexafluoride; pentafluorosulfanylation